La Voz de Michoacán and Those Who Can’t Hear: Discursive Changes About Morelian Deaf People in a Local Newspaper (1948-2014) (Tzintzun, Revista de Estudios Históricos, 2019)
This paper examines how the newspaper La Voz de Michoacán has changedthe way it refers to a sector that has been little analyzed by Mexican historiography:the deaf. The role of the press, in dissemination and modificationof people’s opinion and perspective about this community, is highlightedthrough analyzing documents related to deaf people, and contextualizingthese manuscripts into processes as rehabilitative medical model implementation,subsequently emphasizing human rights and non-discrimination tohearing-impaired people in Morelia.
Keywords: Deaf people; rehabilitation; disability; press; Morelia